Psychological characteristics of caregivers of pediatric patients with chronic rheumatic disease in relation to treatment adherence - Livia de Freitas Keppeke; Juliana Molina; Vanessa Bugni Miotto e Silva; Maria Teresa de Sande e Lemos Ramos Ascensão Terreri; Gerson Dierley Keppeke; Teresa Helena Schoen; Claudio Arnaldo Len (BMC, 2018)
Abstract Background Adherence to treatment for chronic diseases is lower in children than in adults, less extensively studied in children and is associated with multiple related factors. The aim of this study is to perform a descriptive analysis of psycho-cognitive aspects of primary caregivers of pediatric patients with chronic rheumatic diseases, as well as socioeconomic and clinical factors, family functioning and treatment satisfaction. Methods Primary caregivers of 90 patients were included. Pairs (caregiver plus patient) were grouped as presenting good adherence (n = 50) or poor adherence (n = 40) according to the Morisky Adherence Test. Psycho-cognitive aspects were evaluated by Adult Self-Report and Wechsler Adult Intelligence Scale tests. For statistical comparisons, quantitative variables with normal distribution were analyzed by Student's t test, and those with non-Gaussian distribution with the Mann Whitney test. Categorical variables were analyzed by Chi square test. A multivariate logistic regression analysis was performed to estimate the contribution of the independent variables to adherence. Results Compared to caregivers in the good adherence group, caregivers in the poor adherence group were more likely to be classified as clinical on the scales for attention problems and externalizing problems, which include impulsiveness and aggressiveness. They also scored higher on the depressive problem scale. In addition, the average number of children per caregiver and the mean age of caregivers and patients were significantly higher in the poor adherence group, while the proportion of caregivers with higher education was lower. The poor adherence group also included a higher incidence of pediatric patients assuming sole responsibility for managing medications. Economic status, clinical factors, treatment satisfaction, family functioning and caregiver cognitive profile were not related to adherence, except for working memory index. Conclusion Older patients, patients as the one solely responsible for medication management, and caregivers with externalizing problems, were observed to be the most strongly associated to poor adherence. Interventions aimed at adolescent patients are needed. Also, psychological programs and interventional studies to better determine caregivers' behavioral/emotional status, and parent-child relationships are recommended.